The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.4161/cbt.1.1.41
|View full text |Cite
|
Sign up to set email alerts
|

The Mutant p53-Conformation Modifying Drug, CP-31398, Can Induce Apoptosis

Abstract: CP-31398, a styrylquinazoline, emerged from a screen for therapeutic agents that restore a wild-type DNA-binding conformation of mutant p53 to suppress tumors in-vivo (Science 286, 2507, 1999). We investigated the growth inhibitory mechanism of CP-31398 using nine human cancer cell lines containing wild-type, mutant or no p53 expression. Six of nine cell lines underwent apoptosis after exposure to CP-31398, while two cell lines, DLD1 colon cancer and H460 lung cancer, underwent exclusively cell cycle arrest. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
91
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(98 citation statements)
references
References 30 publications
7
91
0
Order By: Relevance
“…However, U251MG and U373MG cells nevertheless showed a strong accumulation of p21 when treated with CP-31398 (Figure 3), suggesting that the reporter assay poorly reflects the transcriptional activation, at least of the p21 gene. In this regard, gene chip analysis revealed that most, but not all, p53 response genes are induced when mutant p53 is stabilized through CP-31398 (Takimoto, 2002). Further, in analogy to our protein data (Figure 3), these authors observed a repression of mdm-2 mRNA expression by high concentrations of CP-31398.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…However, U251MG and U373MG cells nevertheless showed a strong accumulation of p21 when treated with CP-31398 (Figure 3), suggesting that the reporter assay poorly reflects the transcriptional activation, at least of the p21 gene. In this regard, gene chip analysis revealed that most, but not all, p53 response genes are induced when mutant p53 is stabilized through CP-31398 (Takimoto, 2002). Further, in analogy to our protein data (Figure 3), these authors observed a repression of mdm-2 mRNA expression by high concentrations of CP-31398.…”
Section: Discussionsupporting
confidence: 70%
“…This, however, is the mode of action previously proposed for CP-31398 (Foster et al, 1999). Further support for a direct interaction of CP-31398 and p53 comes from EMSA studies showing restoration of the sequence-specific DNA-binding ability of the 273 (Arg-His) p53 mutant by CP-31398 (Takimoto et al, 2002).…”
Section: Discussionmentioning
confidence: 81%
“…NMR studies failed to detect any binding of CP-31398 to the p53 core domain . Interestingly, CP-31398 increases the levels of wild-type p53 protein in cells by preventing its ubiquitination independently of Mdm-2 and p53 phosphorylation (Luu et al, 2002;Takimoto et al, 2002;Wang et al, 2003). CP-31398 affects gene expression and induces cell death both in a p53-dependent and -independent manner (Takimoto et al, 2002;Wischhusen et al, 2003;Wang et al, 2003).…”
Section: Small Molecules That Target Mutant P53mentioning
confidence: 99%
“…This idea has been confirmed in vitro and in vivo in several studies. Synergy has been observed between CP31398 and adriamycin or cisplatin (Takimoto et al, 2002) and between PRIMA-1MET and adriamycin, cisplatin or fludarabine (Nahi et al, 2004;Bykov et al, 2005a). The synergy could result from enhanced expression of mutant p53 induced by chemotherapeutic drugs (Bykov et al, 2005a).…”
Section: Small Molecules That Target Mutant P53mentioning
confidence: 99%
“…Some strategies have focused on the blockade of p53 to reduce toxicity of drugs or radiation (Komarov et al, 1999), whereas others have focused on blocking interactions between p53 and negative regulators such as MDM2 (Bottger et al, 1996(Bottger et al, , 1997Midgley et al, 2000). Yet other strategies have been targeted at mutated p53 to restore some wildtype p53-related transcriptional responses, for example, CP-31398 (Foster et al, 1999;Takimoto et al, 2002b; or Prima1 , or therapies aimed at preferential killing of p53-deficient cells (Hamid et al, 2003;Hecht et al, 2003). The identification of novel regulators such as HAUSP, Pirh2, Parc, Akt, or Sir2 has suggested other points of intervention to modulate p53 activity (Zhou et al, 2001;Vousden and Lu, 2002;Brooks and Gu, 2003;Grossman et al, 2003;Kastan and Zambetti, 2003;Leng et al, 2003;Nikolaev et al, 2003).…”
Section: Introductionmentioning
confidence: 99%